EXPLORATION OF IN VIVO ANTIOXIDANT ACTIVITY OF 50% ETHANOLIC EXTRACT OF SESAMUM INDICUM L. SEED AGAINST HIGH FAT DIET INDUCED RATS - KHAN, ZAFAR JAVED; KHAN, NAEEM AHMAD (International Journal of Current Pharmaceutical Research, 2019)
Objective: The aim of the present study was to investigate the in vivo antioxidant potential of 50% ethanolic extract of Sesamum indicum against high-fat diet-induced rats. Methods: Animals were treated with plant extract for 30 d, and a high-fat diet was given to all groups except plain control, throughout, out the study. And alpha-tocopherol acetate (Vit, E) was used as standard. Pre-treatment with 16 mg/100 gm of body weight of 50% ethanolic extract of Sesamum indicum improved the Superoxide dismutase, catalase, glutathione, and lipid peroxidation levels significantly as compared to control group. Results: The present studies revealed that Sesamum indicum has significant in vivo antioxidant activity and can be used to protect tissue from oxidative stress. The result showed that the activities of SOD, catalase, lipid peroxidase, and glutathione, in the group treated with high-fat diet declined significantly than that of normal group. Conclusion: 50% ethanolic extract of in the dose of Sesamum indicum 16 mg/100 gm of body weight, has improved the SOD, catalase, glutathione, and lipid peroxidase levels significantly, which were comparable with high-fat-diet-induced rats. Based on this study we conclude that the 50% ethanolic extract of Sesamum indicum possesses in vivo antioxidant activity and can be employed in protecting tissue from oxidative stress.